The sequencing of agricultural market reforms in Malawi - Kherallah, Mylene; Kumaresan, Govindan (International Food Policy Research Institute, 1997)
The paper analyzes the welfare impacts of alternative sequencing scenarios of agricultural market reforms in Malawi using a profit maximization approach. The simulation results show that, contrary to the sequencing path adopted in the 1980's, Malawi's Government should have liberalized the maize sector first, followed by the groundnut export sector, and once a supply response was generated, input subsidies could have been phased out, without generating a negative impact on producers' welfare and food security.